Mutual Aid: A Factor of Evolution - Kropotkin, Petr Alekseevich, kniaz, 1842-1921 (Salt Lake City, UT : Project Gutenberg, 2003)
"Mutual Aid: A Factor of Evolution" by Petr Alekseevich Kropotkin is a collection of essays published in 1902. Drawing from observations in Siberia and beyond, Kropotkin challenges social Darwinism's emphasis on competition, arguing instead that cooperation and mutual aid are fundamental forces in nature and human societies. He examines how animals and humans throughout history$1 (Bfrom indigenous peoples to medieval guilds$1 (Bhave survived and thrived through collaboration rather than ruthless competition. This work presents a scientific foundation for anarchist communism while offering insights that influenced evolutionary biology. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/Mutual_Aid:_A_Factor_of_Evolution
Release date is 2003-08-01
Produced by Charles Aldarondo
Keywords: Cooperation; Social groups; Social institutions